x → 0 lim ( x 2 1 + x 1 − x 2 1 − x 1 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It should be 1. LHL=RHL=1
Log in to reply
Yes it should be 1.I also got the answer as 1
Log in to reply
u r making same silly mistake.see my other comment .And the same mistake is there in the solution here.
Helpful graph . (When solving, I accidentally assumed that x 2 1 = x 1 , and factored it out... it's actually equal to ∣ x 1 ∣ .)
Log in to reply
Yup made the same silly mistake :) (x^2)^1/2=|x|
Problem Loading...
Note Loading...
Set Loading...